Collective Action Typologies and Reforestation in Indigenous Community of Biak-Papua - Henry Silka Innah; Didik Suharjito; Arya Hadi Dharmawan; Dudung Darusman (Institut Pertanian Bogor (IPB University), 2013)
While there are issues in deforestation with interesting reports on reforestation in Indonesia's forest policy, the situation in Papua remains understudied. This paper builds on the themes of collective action and reforestation from indigenous people of Papua. Collective action can be understood from various perspectives and one of them can be studied within Gamson's socio-psychology framework from social movement theories. The results showed that: collective action in indigenous people of Biak-Papua was connected to their collective identity, solidarity, consciousness, and was facilitated by micromobilization. There were 4 typologies of collective action for reforestation in Biak: (1) collective action with initiative of collectivity in the group supported by external forces, (2) collective action driven by village leaders that have the authority from the government, (3) collective action driven by informal leaders (genealogical/kinship based traditional leaders), and (4) collective action driven by an outsider that has obtained legitimacy of customary, because of marriages. Taking into account its potentials and dynamics, mutually beneficial collective action is believed to be able to support the success of reforestation and forest management in Papua.